On (?, I)-Statistical Convergence of Order ? of Sequences of Function - Sengul, Hacer; Et, Mikail (Natl Acad Sciences India, 2018)
In this paper, we introduce the concepts of pointwise (lambda, I)-statistical convergence of order alpha and pointwise w(p)(lambda, I)-summability of order alpha. Also some relations between pointwise (lambda, I)-statistical convergence of order alpha and pointwise w(p)(lambda, I)-summability of order alpha are given.
Keywords: I-convergence; Statistical convergence; Sequences of function